Hanseníase: a influência de um programa de atividade física na percepção da qualidade de vida de pessoas acometidas por incapacidades físicas - Barasuol, Aldair Martins (2021)
Hansen's disease, an infection that affects peripheral nerves, and when not diagnosed and treated early, it affects the muscles corresponding to the affected nerves and generates disabilities, which in addition to body physical damage, it also brings with it social, economic problems, stigma, physical inactivity and low quality of life. Describe the leprosy scenario in Brazil and Brazilian administrative regions to know the disease indicators and this research aims to evaluate the influence of a physical activity program on the patients' perception of Quality of Life who have been affected by disabilities resulting from the progression of Hansen's disease clinical picture in the city of Palmas - TO. For this purpose, a data search was made on the situation of Hansen's disease in Brazil and other regions of the country using the GBD database, which resulted in Article I of this research. Afterward, the instruments (WHOQOL-bref and Old) were used to assess the perception of Quality of Life, and the international questionnaire (IPAQ) to assess the level of physical activity, in which the results were used for writing Articles II and III. The sample group of articles I and II comprised patients with physical disabilities resulting from Hansen's disease from two public Health Centers in the community of Palmas. A description of the perception of Quality of Life of all 43 respondents was performed using the data collected by the questionnaires, eventually, they were invited to participate in the physical activity program, which led to the participation of 5 patients from the beginning to the end of the program; therefore, it enabled the analysis of the perception of patients' Quality of Life before and after intervention. Results: Article I - The prevalence of Hansen's disease in the period of study was 28.56 cases per 100 thousand/inhabitants, the incidence of 2.99/100 thousand/inhabitants. and DALY of 1.7 per 100 thousand/inhabitants; the regions of Brazil with the highest rates were the North with a 35.9 prevalence and a 3.5 incidence, followed by the Midwest region with the prevalence of 30.9 and incidence of 3.2. Article II - Among the main results, the Quality of Life ones were considered good, with mean scores that varied between (53-66), with the lowest score of 52.65 (SD ± 12.68) for the domain Physical, which had its facet regarding the best evaluated medical treatment and the sleep and rest aspects with the lowest evaluation. The assessment in the elderly sample group highlighted the facet Death and dying with an average of 36.16 (± 15.66) who got the worst score. Article III - The analysis of perceptions of Quality of Life before and after intervention did not show statistically significant improvements, however, it was possible to observe some improvement in the Physical and Psychological domains, with values ranging between (41-60), and a worsening in the Social Relations domain, which went from a mean score between (61-80) to (41-60). The NAF went from insufficiently active B (n = 4; 80%) to Active (n = 2; 40%) and Very active (n = 3; 60%). This research allowed to identify points that still need attention regarding the aspects analyzed in the perception of Quality of Life of people with disabilities, and besides, it showed that the practice of physical activity as a way of encouraging self-care and group interaction can contribute to improving health and, consequently, Quality of Life.